The Effect of Hypoxic MSC Exosome on IL-10 and SOCS3 Expression - Siti Sundari Sundari; Agung Putra; Titiek Sumarawati; Eko Setiawan; Joko Wahyu Wibowo; Hadi Sarosa (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2026)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by insulin resistance and persistent inflammation. Increased expression of Suppressor of Cytokine Signaling 3 (SOCS3) and decreased Interleukin-10 (IL-10) contribute to the progression of inflammation and impaired insulin signaling. Mesenchymal stem cell-derived exosomes under hypoxic conditions (EH-MSCs) have shown potential anti-inflammatory effects and may improve inflammatory responses in T2DM. Objective: This study aimed to determine the effect of hypoxic mesenchymal stem cell exosomes (EH-MSCs) on IL-10 and SOCS3 expression in Wistar rats with type 2 diabetes mellitus. Methods: This was an in vivo experimental study using a randomized post-test only control group design. Twenty-eight Wistar rats were divided into four groups (n=7 each): negative control (K1), positive control (K2), treatment with intravenous injection of EH-MSCs 250 µL (K3), and treatment with intravenous injection of EH-MSCs 500 µL (K4). IL-10 and SOCS3 expression levels were measured using qRT-PCR on day 30. Data were analyzed using One-Way ANOVA followed by Post Hoc LSD test with a significance level of p<0.05. Results: The mean IL-10 expression was highest in K3 (1.99 ± 0.39), followed by K4 (1.47 ± 0.49), K2 (1.37 ± 0.54), and K1 (1.12 ± 0.31), with a statistically significant difference among groups (p = 0.009). Meanwhile, the mean SOCS3 expression was highest in K1 (1.09 ± 0.41) and lowest in K3 (0.56 ± 0.11), with significant differences among groups (p = 0.018). These findings indicate that EH-MSC administration increased IL-10 expression and decreased SOCS3 expression, particularly at the 250 µL dose. Conclusion: Hypoxic mesenchymal stem cell-derived exosomes significantly increased IL-10 expression and decreased SOCS3 expression in T2DM model rats, with the 250 µL dose showing the most effective anti-inflammatory response. EH-MSCs have potential as a therapeutic strategy for reducing inflammation in T2DM.